Comparative evaluation of bispectral index system after sedation with midazolam and propofol combined with remifentanil versus ketamine in uncooperative during dental procedures - Alireza Eshghi; Mehrnaz Mohammadpour; Nasser Kaviani; Dana Tahririan; Najmeh Akhlaghi (Wolters Kluwer Medknow Publications, 2016)
Background: Proper analgesic agents should be used in combination with sedative agents. Remifentanil is a synthetic narcotic/analgesic agent with a short duration effect and decreases the risk of apnea during recovery. Bispectral index system (BIS) is a new noninvasive technique for the evaluation of the depth of sedation. The aim of present clinical trial was to evaluate and compare the efficacy of intravenous sedation with propofol/midazolam/remifentanil (PMR) in comparison to propofol/midazolam/ketamine (PMK) for dental procedures in children 3-7 years of age. Materials and Methods: In this clinical trial, 32 healthy uncooperative children who were candidates for dental treatments under sedation were randomly divided into two groups. Intravenous sedation was induced with PMR in one group and with PMK in the other group. After injection and during procedure BIS index, heart rate and respiratory rate, blood pressure, and oxygen saturation was evaluated every 5 min. After the procedure, recovery time was measured. Data were analyzed with ANOVA, Friedman, Wilcoxon, and t-test. Results: The BIS value was significantly low in ketamin group (P = 0.003) but respiratory rates and heart rates were same in both groups with no statistical difference (P = 0.884, P = 0.775). The recovery time was significantly shorter in remifentanil group (P = 0.008 and P = 0.003). Conclusion: It can be concluded that intravenous sedation technique with PMR combination induces effective and safe sedation, with less pain and more forgetfulness and a shorter recovery time for children 3-7 years of age during dental procedures.